Gastric antral vascular ectasia should not be overlooked in erythropoietin resistance: a series of case reports - Rimševičius, Laurynas; Galkauskas, Domantas; Lavinskas, Julius; Šestelinska, Evelina; Mačionienė, Ernesta; Laučytė-Cibulskienė, Agnė; Rėkutė, Skirmantė; Miglinas, Marius (Acta medica Lituanica, 2019)
Background. Gastric antral vascular ectasia (GAVE) is currently recognized as an important cause of upper gastrointestinal (GI) haemorrhage, being responsible for about 4% of non-variceal upper GI haemorrhages and typically presents in middle-aged females. GAVE, also called “watermelon stomach”, is diagnosed through esophagogastroduodenoscopy and is characterized by the presence of visible columns of red tortuous enlarged vessels along the longitudinal folds of the antrum. The pathogenesis is still obscure and many hypotheses have been proposed such as mechanical stress, humoral and autoimmune factors. In the last two decades, numerous therapeutic strategies have been proposed, including surgical, endoscopic, and medical choices, yet successful treatment of GAVE continues to be a challenge. Currently, given the rapid response, safety, and efficacy, endoscopic ablative modalities have largely usurped medical treatments as first-line therapy, particularly using argon plasma coagulation. The actual GAVE prevalence in patients with end-stage renal disease (ESRD) is not clear, yet in difficult cases it should be considered as a cause of erythropoietin resistance. Case presentation. We report four clinical cases of GAVE syndrome patients diagnosed with stage 4 to 5 chronic kidney disease. All patients presented with anaemia and GI haemorrhage, the origin of which turned out to be GAVE syndrome. Conclusions. GAVE syndrome is a serious condition in ESRD patients, especially in those presenting with treatment-refractory anaemia. Realization of its aetiology and characteristics is essential to suspect, diagnose, and treat gastric ectasia. Only proper diagnosis and well-timed disease treatment can significantly improve a patient’s medical condition and future prognosis.